Intellectual Disability and Experiencing Happiness - PORCZYŃSKA-CISZEWSKA, ANNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Anna Porczyńska-Ciszewska, Intellectual Disability and Experiencing Happiness. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019. Pp. 51-66. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.24.03 Although it may be challenging to unambiguously recognize and define it, the notion of experiencing happiness, a constituent of psychological well-being, is undoubtedly one of the key traits featuring every person, whether intellectually fit or disabled. The feeling of happiness plays a significant role when coping with various types of situations including also the circumstances faced by an intellectually disabled person. Due to the diversity and multeity of the dimensions where it occurs, the experience of happiness can be subject of analyses from various stances, including the viewpoint of an intellectually disabled person. It seems that the disabled individual’s ability to deal with difficulties, which also influences efficiency of the rehabilitation process, is actually determined by the feelings of happiness, content and optimism, all of which remain in a relation with one’s personality, life situation, and conditions in which they live. The article draws attention to the subject of experiencing happiness by and psychological well-being of intellectually disabled people. It emphasizes the possibility of both theoretical and practical applications of assumptions of positive psychology as a requisite condition for the optimization of functioning of intellectually disabled people. Beyond any doubt, due care for the intellectually disabled people’s experience of happiness and psychological wellbeing is one of the most crucial requirements of their rehabilitation process as “positive states of mind (…) provide the power to struggle with adversities of life”